Relevant issues of clinical pattern and treatment of acute suppurative otitis media - A. I. Kryukov; N. L. Kunelskaya; A. V. Gurov; Z. G. Elchueva; G. N. Izotova; D. L. Muratov; S. S. Sokolov (Медицинский совет, 2015)
The contemporary otorhinolaryngology is faced with the problem of prevention, treatment and rehabilitation of patients with auditory disorders due to various causes. Overall, acute inflammatory diseases of the middle ear account for quite a high percentage of ear pathology; the type of disorder often results in a temporary disability as well as chronic inflammatory process, onset of various complications (otogenic intracranial, sepsis, labyrinthitis, facial neuropathy et al.) and subsequently - persistent disability of the patient [3].